(untitled) (Research, Society and Development, 2020)
Objective: To analyze the nursing team’s understanding of risk factors and good practices related to the prevention of delirium in critically ill patients. Methods: Cross-sectional study conducted with the nursing team of Intensive Care Units of a tertiary and university hospital in Porto Alegre/RS. Results: It was found that a large part of the nursing team is aware of the risk factors for delirium in the ICU, such as noise, excessive sedation, increased risk of infection, increased permanence and mortality. Likewise, they understand the benefits of good practices, such as promoting comfort, adequate sedation, presence of a family member, guidance and daily evaluations through delirium scales. Conclusion: It is noticed that the nursing team understands delirium in critically ill patients, the conditions that favor its development, its impact on the length of stay in the ICU and mortality. However, it is observed that improvements are still needed regarding good practices in the management of delirium.